Fate of pulpectomized deciduous teeth: Bilateral odontogenic cyst? - B Sandhyarani; Hina Noorani; P K Shivaprakash; A Huddar Dayanand (Wolters Kluwer Medknow Publications, 2016)
Pulpectomy is preferably more conservative treatment option than the extraction of deciduous teeth despite few undesirable consequences of obturating materials of which odontogenic cysts are one. This article aims to report a case of an 11-year-old female child having bilateral odontogenic cysts, i.e., radicular and infected dentigerous cyst followed by pulpectomy of deciduous molars using zinc oxide eugenol which was surgically enucleated and followed up to 6 months until satisfactory healing of bone was observed. The article also emphasizes on the importance of regular follow-up of the pulpectomized tooth which can be harmful otherwise.